Advances in Experimental Medicine and Biology
DOI: 10.1007/978-0-387-74087-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Milk Lipoprotein Membranes and Their Imperative Enzymes

Abstract: There are two main sources of lipoprotein membranes in milk: the relatively well-defined milk fat globule membrane (MFGM) that covers the milk fat globules, and the much less attended lipoprotein source, in the form of vesicles floating in the milk serum. We challenge the common view that the milk serum lipoprotein membrane (MSLM) is secondly derived from the MFGM and present a different view suggesting that it represents Golgi-derived vesicles that are released intact to milk. The potential role of enzymes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…Tissue sections of mammary glands of mastitic animal revealed low or no activity of alkaline phosphatase. In accordance with our results, Silanikove andShapiro (2007) andEL sayed et al (2009) have shown that AP is located almost on the mammary epithelial cells apical membrane. This weak activity of AP in mastitic tissues may be related with deactivation of this enzyme owing to negative regulatory process of mammary gland as a result of negative effects of pathogens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tissue sections of mammary glands of mastitic animal revealed low or no activity of alkaline phosphatase. In accordance with our results, Silanikove andShapiro (2007) andEL sayed et al (2009) have shown that AP is located almost on the mammary epithelial cells apical membrane. This weak activity of AP in mastitic tissues may be related with deactivation of this enzyme owing to negative regulatory process of mammary gland as a result of negative effects of pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…This weak activity of AP in mastitic tissues may be related with deactivation of this enzyme owing to negative regulatory process of mammary gland as a result of negative effects of pathogens. The weak activity of alkaline phosphatase enzyme could be due to impaired milk secretory mechanism (Silanikove, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Milk protein synthesis in mammary tissue is a complex mechanism under the influence of local and systemic hormones along with some other factors those affect milk yield (Khaliq andHussain et al, 2010). The weak AP activity and protein density that observed in this work in singly isolated S.aureus mastitic tissue sections were observed previously by Hassan (2004); Silanikove (2008);El-Sayed et al (2009); Hussain et al (2012c) and Hussain et al (2013) which attributed to the degenerative changes of mammary epithelium with connective tissue proliferation and impaired activity of endoplasmic reticulum that induced by microbial agents. These degenerated mammary cells encompassing the active cellular protein was substituted by the spread of connective tissue under the bacterial toxins effect which resulted in poor biosynthetic capacity of udder and decreases cellular differentiation.…”
Section: Discussionsupporting
confidence: 80%
“…Nucleobases are the nitrogenous bases that are the basic units of the genetic code (adenine (A), cytosine (C), guanine (G), thymine (T), and uracil (U)). They are essential for cellular function, acting as mediators of chemical energy transfer, signal transduction, and growth regulators [356,357].…”
Section: Nucleotides and Nucleosidesmentioning
confidence: 99%